RABITHAH MA'AHID ISLAMIYYAH PBNU DAN PENERAPAN PROTOKOL KESEHATAN DI PESANTREN PADA MASA PANDEMI - Abdul Ghofarrozin; Tutik Nurul Janah (Academic Journal of Islamic Principles and Philosophy, 2021)
Since the arrival of the Covid-19 pandemic in Indonesia, the education process has been carried out online for all levels. However, this policy cannot be applied to pesantren educational institutions that continue to conduct offline learning. The question is how can Islamic boarding schools (pesantren) survive the Covid-19 pandemic ?. There are institutions that play an active role in controlling and preventing it. Nahdlatul Ulama' (NU) as the largest community organization in Indonesia, has aÂ Rabithah Ma'ahid Islamiyyah(RMI) which focuses on sheltering thousands of Islamic boarding schools (pesantren) throughout Indonesia. This article focuses on looking at the role of RMI in assisting Islamic boarding schools in dealing with the Covid-19 pandemic. By using a qualitative-descriptive approach that bases data on interviews, observation and documentation, this article shows that RMI has an important role in assisting Islamic boarding schools against Covid-19. First, at the prevention stage, RMI PBNU gave an appeal through official notifications to all pesantren, socializing health protocols with flayers, pamphlets, etc. Second, at the detect and respond stage, RMI PBNU implemented a task force training program (SATGAS) for handling COVID-19 at Islamic boarding schools, providing virus detection machines (PCR machines), together with the Nahdlatul Ulama Doctors Association (PDNU) accompanying COVID-19 cases in Islamic boarding schools.Â